Drug Delivery System Approaches for Rheumatoid Arthritis Treatment: A Review - Garhwal, Anushka; Kendya, Priyadarshi; Soni, Sakshi; Kori, Shivam; Soni, Vandana; Kashaw, Sushil K. (Mini Reviews in Medicinal Chemistry, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that has traditionally been treated using a variety of pharmacological compounds. However, the effectiveness of these treatments is often limited due to challenges associated with their administration. Oral and parenteral routes of drug delivery are often restricted due to issues such as low bioavailability, rapid metabolism, poor absorption, first-pass effect, and severe side effects. In recent years, nanocarrier-based delivery methods have emerged as a promising alternative for overcoming these challenges. Nanocarriers, including nanoparticles, dendrimers, micelles, nanoemulsions, and stimuli-sensitive carriers, possess unique properties that enable efficient drug delivery and targeted therapy. Using nanocarriers makes it possible to circumvent traditional administration routes' limitations. One of the key advantages of nanocarrier- based delivery is the ability to overcome resistance or intolerance to traditional antirheumatic therapies. Moreover, nanocarriers offer improved drug stability, controlled release kinetics, and enhanced solubility, optimizing the therapeutic effect. They can also protect the encapsulated drug, prolonging its circulation time and facilitating sustained release at the target site. This targeted delivery approach ensures a higher concentration of the therapeutic agent at the site of inflammation, leading to improved therapeutic outcomes. This article explores potential developments in nanotherapeutic regimens for RA while providing a comprehensive summary of current approaches based on novel drug delivery systems. In conclusion, nanocarrier-based drug delivery systems have emerged as a promising solution for improving the treatment of rheumatoid arthritis. Further advancements in nanotechnology hold promise for enhancing the efficacy and safety of RA therapies, offering new hope for patients suffering from this debilitating disease.
Keywords: novel therapeutic agents